Reactivation of relationships with customers in the case of telecommunications: a qualitative study - Lopes, Luisa (2020)
Overall there has been a scarce focus on why customers come back after the relationship ended when customer regain and win-back are an important part of a customer relationship management strategy. Determinants of customer relationship reactivation are addressed based on ending literature and equity theory. A case study, of a telecommunications company delivering a mix of goods and services, is described and includes a total of 40 interviews in the marketing and customer service departments and with customers. Telecommunications explore reactivation possibilities mostly on the relationship’s rupture phase and with a retention focus. The most relevant reactivation determinants are considered to be customer characteristics (as age, involvement, and variety seeking), cognitive factors (as offer’s value, procedures, and satisfaction), reasons to switch and alternatives. The contribution of this empirical study is to advance knowledge about antecedents